The primary function of Six5 of Fusarium oxysporum is to facilitate Avr2 activity by together manipulating the size exclusion limit of plasmodesmata - Blekemolen, Mila C.; Cao, Lingxue; Tintor, Nico; de Groot, Tamara; Papp, Diana; Faulkner, Christine; Takken, Frank L. W. (Frontiers in Plant Science, 2022)
Pathogens produce effector proteins to manipulate their hosts. Whereas most effectors act autonomously, some fungal effectors act in pairs and rely on each other for function. During colonization of the plant vasculature, the root-infecting fungus Fusarium oxysporum (Fo) produces fourteen so-called Secreted in Xylem (SIX) effectors. Two of these effector genes, Avr2 (Six3) and Six5 form a gene pair on the pathogenicity chromosome of the tomato infecting Fo strain. Avr2 has been shown to suppress plant defence responses and is required for full pathogenicity. Although Six5 and Avr2 together manipulate the size exclusion limit of plasmodesmata to facilitate cell-to-cell movement of Avr2, it is unclear whether Six5 has additional functions as well. To investigate the role of Six5 we generated transgenic Arabidopsis lines expressing Six5. Notably, increased susceptibility during early stages of infection was observed in these Six5 lines, but only to Fo strains expressing Avr2 and not to wild-type Arabidopsis-infecting Fo strains lacking this effector gene. Furthermore, neither PAMP-triggered defence responses such as ROS accumulation and callose deposition upon treatment with Flg22, NLP (Necrosis and ethylene-inducing peptide 1-like protein) or chitosan, nor susceptibility to other plant pathogens, such as the bacterium Pseudomonas syringae or the fungus Verticilium dahlia, were affected by Six5 expression. Further investigation of the ability of the Avr2/Six5 effector pair to manipulate plasmodesmata (PD) revealed that it not only permits cell-to-cell movement of Avr2, but also facilitates movement of two additional effectors, Six6 and Six8. Moreover, although Avr2/Six5 expand the size exclusion limit of plasmodesmata (i.e., gating) to permit movement of a 2xFP fusion protein (53 kDa), a larger variant, 3xFP protein (80 kDa), did not move to neighbouring cells. The PD manipulation mechanism employed by Avr2/Six5 did not involve alteration of callose homeostasis in these structures. In conclusion, the primary function of Six5 appears to function together with Avr2 to increase the size exclusion limit of plasmodesmata by an unknown mechanism to facilitate cell-to-cell movement of Fo effectors.